2022
DOI: 10.3389/fpsyg.2021.774148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Control on Subjective Well-Being: Examining the Moderating Role of Trait and State Motivation

Abstract: It is well documented that self-control has a positive effect on individuals’ subjective well-being. However, little research has focused on the moderators underlying this relationship. The present research used two studies to examine the moderating role of both trait and state motivation on the relationship between self-control and subjective well-being using psychometric and experimental models, respectively. In Study 1, we explored whether trait motivation (including promotion vs. prevention motivation) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A large body of evidence has shown the importance of self-control for people’s life adaptation. For example, individuals with higher levels of self-control generally reported higher levels of subjective wellbeing and a better state of health ( 16 , 17 ). Self-control, as an internal factor, is closely related to individual’s mental health.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has shown the importance of self-control for people’s life adaptation. For example, individuals with higher levels of self-control generally reported higher levels of subjective wellbeing and a better state of health ( 16 , 17 ). Self-control, as an internal factor, is closely related to individual’s mental health.…”
Section: Introductionmentioning
confidence: 99%
“…According to our knowledge, a variety studies have been conducted to evaluate the effects of external factors, such as self-esteem [ 1 , 22 , 23 ], self-control [ 24 26 ], depression, anxiety [ 6 , 27 ] and personality traits, on SWB of high school students. But few articles explore the interactions of internal factors of SWB.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that individuals with high self‐control tend to have higher life satisfaction (Dou et al, 2016). Studies have also shown that constant negative affective state may reduce one's self‐control ability as dealing with the negative affective state can result in ego depletion and self‐control failure (Lee et al, 2022; Zhao et al, 2022). For example, students who struggle with academic anxiety would routinely check their performance.…”
Section: Introductionmentioning
confidence: 99%